(untitled) (Economic studies journal, 2019)
The purpose of this paper is to evaluate the financial performance of the Libyan social security fund (SSF) and to what extent the system is able to serve the community in the long run. The study relies on the financial data of SSF for the period between 1998 to 2007. Data was examined using trend analysis across years, financial ratios, and in the light of economic indicators. In addition, statistical model is developed to predict whether SSF is making surplus or suffering financial deficit. The study concludes that SSF is suffering some financial difficulties and the return on its investments is not worth mentioning. The study reveals that government intervening was one of the major factors affecting negatively SSF performance with other factors such as the lack of collecting receivables from the government and from people who exploit SSF real-estates.